PENGEMBANGAN MULTIMEDIA INTERAKTIF IPA BERORIENTASI GUIDED INQUIRY PADA MATERI SISTEM PERNAPASAN MANUSIA KELAS V SDN KEBONSARI 3 MALANG - Taufiq Nuril Akbar (Graduate School of Universitas Negeri Malang, 2016)
Multimedia interactive is a computerizing learning methodology covered in compact disc (CD) which contains of an interactive application and some menu which can be clicked to show some necessary information. This research and development are based on Lee & Owen theories. They use some following steps; (1) analysis assessment, (2) designs, (3) development, (4) implementation, and (5) evaluation. Because of This model having focus on evolving multimedia, it becomes the most important reasons in carrying on this research in order to discover interactive multimedia product for science study according to guided inquiry about respiratory system in the fifth grade of state elementary school. The result of this research has shown that this certain method, interactive multimedia development, is qualified enough to apply in learning process at school. It is gained from analysis of product validation assessments with 90 % reaching valid category, analysis of product appealing assessments with 93, 3 % of achieving appealing level, analysis of product practicality assessments with 92 % getting practical category, and analysis of product effectiveness assessment with 88, and 5 % with achieving effective level.Multimedia interaktif merupakan media pembelajaran berbasis komputer yang dikemas dalam sebuah CD (Compact Disk) yang di dalamnya terdapat aplikasi interaktif dan juga mempunyai menu yang dapat diklik untuk menampilkan suatu informasi tertentu. Penelitian dan pengembangan ini menggunakan model Lee & Owens. Langkah-langkah pengembangan model Lee & Owens yaitu: (1) penilaian analisis, (2) desain, (3) pengembangan, (4) implementasi, dan (5) evaluasi. Alasan pemilihan model ini karena model ini merupakan model pengembangan yang dikhususkan untuk mengembangkan multimedia. Tujuan penelitian dan pengembangan ini untuk menghasilkan produk multimedia interaktif IPA yang berorientasi guided inquiry materi sistem pernapasan manusia kelas V Sekolah Dasar. Hasil penelitian ini menunjukkan bahwa multimedia interaktif ini termasuk dalam kualifikasi layak untuk digunakan dalam pembelajaran. Hal ini ditunjukkan dengan analisis penilaian kevalidan produk yang mencapai persentase 90% yang masuk kategori “valid”, analisis penilaian kemenarikan produk yang mencapai persentase 93,3% yang masuk kategori “menarik”, analisis penilaian kepraktisan produk yang mencapai persentase 92% yang masuk kategori “praktis”, dan analisis penilaian keefektifan produk yang mencapai persentase 88,5% yang masuk kategori “efektif”.